2022
DOI: 10.1021/acsabm.2c00301
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Electrochemical Immunosensor Platforms for Dual Detection of SARS-CoV-2 Antigen and Antibody based on Gold Nanoparticle Functionalized Graphene Oxide Nanocomposites

Abstract: In this work, we report a facile synthesis of graphene oxide–gold (GO–Au) nanocomposites by electrodeposition. The fabricated electrochemical immunosensors are utilized for the dual detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antigen and SARS-CoV-2 antibody. The GO–Au nanocomposites has been characterized by UV–vis spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), cyclic voltammetry (CV), differential pulse voltammetry (DPV), and electrochemical impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…The detection of the SARS-CoV-2 virus using combinations of electrochemical techniques, such as voltametric [ 4 , 47 , 48 , 49 , 51 , 53 , 54 ], amperometric [ 5 , 9 , 52 ] and impedimetric [ 6 , 7 , 10 , 27 , 55 ] techniques, was explored for the determination of different bioreceptors of SARS-CoV-2. In comparison to previous studies reporting on the development of different techniques [ 8 , 56 , 57 , 58 , 59 ], the advantages of our label-free impedimetric immunosensor are listed as the simple preparation procedure with short preparation time (i.e., 3 h) and rapid analysis (only 6 min). Moreover, no surface modification using nanomaterials, such as graphene [ 8 , 56 ], graphene oxide [ 57 ] or gold nanoparticles [ 57 , 58 , 59 ], was applied in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of the SARS-CoV-2 virus using combinations of electrochemical techniques, such as voltametric [ 4 , 47 , 48 , 49 , 51 , 53 , 54 ], amperometric [ 5 , 9 , 52 ] and impedimetric [ 6 , 7 , 10 , 27 , 55 ] techniques, was explored for the determination of different bioreceptors of SARS-CoV-2. In comparison to previous studies reporting on the development of different techniques [ 8 , 56 , 57 , 58 , 59 ], the advantages of our label-free impedimetric immunosensor are listed as the simple preparation procedure with short preparation time (i.e., 3 h) and rapid analysis (only 6 min). Moreover, no surface modification using nanomaterials, such as graphene [ 8 , 56 ], graphene oxide [ 57 ] or gold nanoparticles [ 57 , 58 , 59 ], was applied in our study.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to previous studies reporting on the development of different techniques [ 8 , 56 , 57 , 58 , 59 ], the advantages of our label-free impedimetric immunosensor are listed as the simple preparation procedure with short preparation time (i.e., 3 h) and rapid analysis (only 6 min). Moreover, no surface modification using nanomaterials, such as graphene [ 8 , 56 ], graphene oxide [ 57 ] or gold nanoparticles [ 57 , 58 , 59 ], was applied in our study. In contrast to optical detection of SARS-CoV-2 [ 59 , 60 ], our assay is easy to apply without requiring any extra labels (such as fluorescent dye, peptide etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these advantages, numerous studies have reported the electrochemical-immunosensor-based detection of the SARS-CoV-2 N protein. 13 Accordingly, Salahandish et al fabricated a carbon/graphene @PEDOT:PSS hybrid ink, 14 Eissa et al prepared gold nanoparticles 15 and fabricated a cotton-tipped platform, 16 Karaman et al developed a bismuth tungstate/bismuth sulfide composite (Bi 2 WO 6 /Bi 2 S 3 ), 17 and Sadique et al reported a gold-nanoparticle-functionalized graphene oxide (GO-Au) nanocomposite 18 for the electrochemical determination of SARS-CoV-2 N protein with limit of detections (LODs) of 116 fg mL À1 , 0.4 pg mL À1 , 0.8 pg mL À1 , 3 fg mL À1 , and 3.99 ag mL À1 respectively. Two-dimensional (2D) nanomaterials such as transition metal dichalcogenides (TMDs) have been widely exploited as electrode surface materials owing to their exceptional characteristics, such as high surface-area-to-volume ratio, structural stability, and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing pandemic of COVID-19 needs diagnostic tools that are more accurate, sensitive, simple, and affordable. To increase the detection accuracy and sensitivity, new methods are being developed, including signal amplification, electrochemical sensors, chemiluminescent sensors, microfluidic immunosensors, and graphene-based biosensors. In these immunosensors, antibodies or aptamers are pretreated with a signal amplification material, which captures target antigens and requires a long incubation time or requires specific equipment for result readout. Noble metal nanoparticles have high catalytic efficiency, high stability in complex environments, and easy production, which make them promising for signal amplification in colorimetric immunoassays and can significantly improve the sensitivity of ELISAs and LFAs. The peroxidase mimics with ultrahigh catalytic activities can quickly generate blue molecules by catalyzing the oxidation of 3,3′,5,5′-tetramethylbenzidine (TMB) with H 2 O 2 in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%